The hip trial: psychosocial consequences for mothers of using ultrasound to manage infants with developmental hip dysplasia. Issue 1 (21st December 2004) - Gardner, F; Dezateux, C; Elbourne, D; Gray, A; King, A; Quinn, A
Abstract : Background: The hip trial aimed to assess clinical effectiveness, economic and psychosocial costs, and benefits of ultrasound imaging (US) compared with conventional clinical assessment alone to guide the management of infants with neonatal hip instability. Objective: To report on psychosocial consequences for mothers and the developing mother-child relationship of US, and associations between abduction splinting and maternal psychosocial distress. Design: Multicentre randomised controlled trial. Setting: Thirty three hospitals in the United Kingdom and Ireland. Participants, interventions: A total of 629 infants with neonatal hip instability randomised to US examination or clinical assessment alone before treatment decision. Questionnaires were completed by 561 (89%) mothers at 8 weeks and 494 (79%) at 1 year. Main outcome measures: Anxiety, postnatal depression, parenting stress assessed by standardised questionnaires. Maternal concerns about hip problems were assessed using the Infant hip worries inventory. Results: At 8 weeks, there were no differences between US and non-US groups of the trial in maternal anxiety (mean difference (MD) −1.2, 95% confidence interval (CI) −3.2 to 0.8), depression (MD 0.0, 95% CI −0.7 to 0.8), parenting stress (MD −1.2, 95% CI −2.8 to 0.4), or other measures. The same pattern was evident at 1 year. In an explanatory analysis, early splinting was associated with increased anxiety at 8 weeks (MD 3.8, 95% CI 1.7 to 5.9) and increased level of hip worries at 8 weeks (MD 6.8, 95% CI 5.6 to 7.9) and 1 year (MD 1.3, 95% CI 0.3 to 2.4). Conclusions: Although early splinting is associated with maternal anxieties, US is not associated with any increase or reduction in psychosocial effects on mothers. Together with the clinical findings, this suggests that the use of US allows reduction in splinting rates without increased risk of adverse clinical or psychosocial outcomes.